Do implicit evaluations reflect unconscious attitudes?. Issue 1 (24th January 2014) - Hahn, Adam; Gawronski, Bertram
Abstract: We extend Newell & Shanks' (N&S's) arguments to the question of whether implicit evaluations reflect unconscious attitudes. We argue that correspondence to explicit evaluations fails to meet the criteria of relevance and sensitivity. When awareness is measured adequately and in line with N&S's criteria, there is compelling evidence that people are consciously aware of their implicit evaluations.